Pelaksanaan Pembelajaran Melukis di Kelompok B1 TK Islam Az-Zahra Tahun Ajaran 2023/2024 - Adam Wahida; Endang Widiyastuti; Mabruroh Firdausi An-nur (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to: (1) describe the learning process of painting for early childhood in group B1 of Az-Zahra Islamic Kindergarten in the 2023/2024 school year, and (2) analyze the form of work produced by group B1 students of Az-Zahra Islamic Kindergarten in the 2023/2024 school year. This research uses a qualitative descriptive approach with a case study method. Sources of research data include learning activities, informants (group B1 teachers and principals), and documents (observation notes, lesson plans, lesson plans, and paintings). The sampling technique was done by purposive sampling, and data collection used observation techniques, document analysis, and interviews. Data validity was tested using source triangulation, and data analysis used a flow analysis model. The results showed that: (1) the analysis of the learning process of painting in group B1 uses the development of Prosem, RPPm, and RPPh. However, learning objectives have not been clearly designed and written in RPPh even though they are in accordance with the Basic Competencies of Art. Learning media and evaluation have been done well, although the checklist instrument for painting activities has not been separated from other activities. (2) Analysis of the results of painting works is carried out based on the elements of painting, the theory of periodization of children's art development, and the typology of children's drawings. Students' works show good creativity, especially in visual elements, with the majority of children at the pre-chart or chart stage, and visual image types dominate.